Chemical and Biological Characterization of Erigeron Floribundus (Kunth) Sch.Bip Extracts Obtained by Four Isolation Procedures. (21st November 2020) - Dall'Acqua, Stefano; Kumar, Gourav; Sinan, Kouadio Ibrahime; Sut, Stefania; Ferrarese, Irene; Mahomoodally, Mohamad Fawzi; Lobine, Devina; Etienne, Ouattara Katinan; Zengin, Gokhan
Abstract: In the present investigation, extracts of Erigeron floribundus leaves obtained by four isolation procedures, including homogenizer-assisted extraction, maceration, sonication and Soxhlet extraction, were compared for their qualitative and quantitative phytochemical composition as well as for their antioxidant and enzyme inhibitory activities. The total phenolic, phenolic acid and flavanol contents were highest in homogenizer-assisted extraction, while maceration contained slightly higher total flavanol content. High-performance liquid chromatography – mass spectrometry (HPLC-DAD-MS n ) analysis revealed that the hydroxycinnamic esters of quinic acids were the most abundant constituents in the isolates. The results showed that the extracts are promising sources of antioxidants with the homogenizer-assisted approach the most suitable. The extracts displayed notable enzyme inhibitory effects against acetylcholinesterases (7.98 ± 0.12 to 8.40 ± 0.09 mg galatamine equivalents (GALAE)/g extract) and tyrosinase (122.73 ± 0.43 to 111.36 ± 1.65 mg kojic acid equivalents (KAE)/g extract). In conclusion, the results demonstrate promising biological activities of E. floribundus isolates obtained via innovative extraction techniques, thereby offering preliminary information for the validation of the traditional medicinal uses of this plant.